Feasibility analysis of clean utilization of kitchen waste oil and lignite by co-fermentation treatment. (15th April 2023) - Guo, Hongyu; Song, Bo; Xia, Daping; Deng, Ze; Chen, Linyong; Wang, Yongjun; Zhao, Weizhong
Abstract: In order to improve the efficiency of biomethane production through lignite anaerobic fermentation and perform the treatment and application of kitchen waste oil (KWO), different KWO to lignite ratios were used for combined anaerobic fermentation of biomethane. Biogas production characteristics, fermentation broth, and solid residue utilization properties of co-fermentation were analyzed using liquid fatty acid, thermogravimetric (TG), and combustion flue gas tests. The experimental results show that the co-anaerobic fermentation of KWO and lignite can improve the biogenic methane production, and the ratio of the two will also affect the biogenic methane production. Among them, the biogenic methane production by the co-anaerobic fermentation of 1.2 g KWO and 20 g of lignite is the largest, which is 377.86% higher than that by the anaerobic fermentation of single lignite. According to the three-dimensional fluorescence spectrum analysis, the fermentation substrate with the highest biogenic methane production contains more fulvic acid, tryptophan, lysine, phenol hydroxyl, ketone carbonyl, carbonyl, and other groups. In the change of fatty acid content before and after anaerobic fermentation, the content of palmitic acid, stearic acid, oleic acid, and other non-degradable fatty acids contained in KWO significantly decreased, and the volatile fatty acids significantly increased. After anaerobic fermentation, the volatilization analysis temperature, ignition point, and combustion temperature of residual coal are advanced, and the combustion is more stable. At the same time, the emission of combustion pollution gas of residual coal after fermentation is significantly reduced, which is conducive to the clean utilization of lignite. Graphical abstract: Image 1 Highlights: Co-anaerobic fermentation of KWO and lignite to promote biomethane. KWO is biodegraded by anaerobic fermentation. The combustion performance of solid residue is improved. The emission of polluting gases from the combustion of solid residues is reduced.